Microbial degradation of paddy (Oryza sativa) straw by submerged state fermentation - VERMA, ISHITA; KATYAL, PRIYA (The Indian Journal of Agricultural Sciences, 2024)
This study elucidates the effective lignocellulose degrading potential of microbial consortium by using paddy straw as the sole source under submerged fermentation conditions. Straw degradation was enhanced by bioaugmentation procedures where consortia of isolated and standard cultures resulted in maximum enzyme activities of endoglucanase (1 U/ml), exoglucanase (1.31 U/ml), β-glucosidase (2.42 U/ml), xylanase (12.63 U/ml) and manganese peroxidase (5.43 U/ml) after 28 days of incubation along with laccase (4.36 U/ml) and lignin peroxidase (6.71 U/ml) after 21 days of incubation. By the action of consortium, maximum reduction of cellulose, hemicellulose and lignin was found to be 35.31, 22.50 and 44.72%, respectively after 28 days of incubation. A significant increase in percentage loss in dry matter of paddy straw was observed till 4 weeks of fermentation. Field emission scanning electron microscope (FE-SEM) micrographs revealed sufficient loosening of cellulose and hemicellulose showing successful degradation of straw tissue. Overall, the above stated findings emphasize on potential of lignocellulosic microorganisms to be used as an alternative to traditional stubble burning practice. Although, these extracellular enzymes are well equipped in breaking down lignocelluloses to their monomeric or oligomeric subunits, but they may not be exploited at commercial level due to very slow rate of reaction. The efficacy of these cultures for straw degradation in field condition further needs elaborative experimental trials as environmental parameters are quite variable in the field.